Out of the Freezer and into the Policy Fire: Quandaries in Reproductive Cryopreservation - Feinberg, Rebecca (The Hastings Center report, 2019)
The field of assisted reproduction is advancing rapidly and is ripe for regulation and guidance. In 2018, over four thousand frozen eggs and embryos were lost to approximately one thousand patients at Ahuja University Hospital in Cleveland, Ohio, due to an accidental thaw of a cryopreservation tank. The precedent that will be set by the Ahuja class-action case is significant for both past events and future possibilities and is core to the discussion of policy involving the cryopreservation of gametes and embryos.